In-Situ Nitrogen Doping of the TiO2 Photocatalyst Deposited by PEALD for Visible Light Activity - 饶志鹏 万军 李超波 陈波 刘键 黄成强 夏洋 (等离子体科学与技术：英文版, 2014)
In this paper, an N-doped titanium oxide （TiO2） photocatalyst is deposited by a plasma-enhanced atomic layer deposition （PEALD） system through the in-situ doping method. X-ray photoelectron spectroscopy （XPS） analysis indicates that substitutional nitrogen atoms （-395.9 eV） with 1 atom% are effectively doped into TiO2 films. UV-VIS spectrometry shows that the in-situ nitrogen doping method indeed enhances the visible-activity of TiO2 films in the 425-550 nm range, and the results of the performance tests of the N-doped TiO2 films also imply that the photocatalysis activity is improved by in-situ doping. The in-situ doping mechanism of the N-doped TiO2 film is suggested according to the XPS results and the typical atomic layer deposition process.